2020
DOI: 10.3390/math8050699
|View full text |Cite
|
Sign up to set email alerts
|

Can You Identify These Celebrities? A Network Analysis on Differences between Word and Face Recognition

Abstract: Face recognition is located in the fusiform gyrus, which is also related to other tasks such word recognition. Although these two processes have several similarities, there are remarkable differences that include a vast range of approaches, which results from different groups of participants. This research aims to examine how the word-processing system processes faces at different moments and vice versa. Two experiments were carried out. Experiment 1 allowed us to examine the classical discrimination task, whi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 46 publications
1
11
0
Order By: Relevance
“…Participants were instructed to identify international celebrities or personalities by name or face and discard unknown stimuli. In the study two simple tasks were used with 28 test stimuli and 28 distractors with repeated measures (with a final total of 224 stimuli), selected from a previous study with University students from Brazil, Spain, and the USA [ 34 ]. Google frequency searches were also employed as a measure of frequency of the stimuli, as suggested in previous literature [ 40 , 43 , 44 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Participants were instructed to identify international celebrities or personalities by name or face and discard unknown stimuli. In the study two simple tasks were used with 28 test stimuli and 28 distractors with repeated measures (with a final total of 224 stimuli), selected from a previous study with University students from Brazil, Spain, and the USA [ 34 ]. Google frequency searches were also employed as a measure of frequency of the stimuli, as suggested in previous literature [ 40 , 43 , 44 ].…”
Section: Methodsmentioning
confidence: 99%
“…This could be of interest for the comparison of two related but different stimuli, such as faces and their associated names. Previous studies based on cognitive tasks have employed network analysis to illustrate the connectivity between word and name recognition processes [ 34 ]. A supplementary strategy to this approach is proposed in this work: the exponentially modified Gaussian distribution (ex-Gaussian).…”
Section: Introductionmentioning
confidence: 99%
“…Retrieving memory of highly familiar faces may well invoke other non-perceptual connections that were established in the process of familiarization. A case in point is a recent study by Moret-Tatay et al ( 2020 ), who demonstrated that the associative links between face and name for celebrities can be asymmetrical, where the magnitude of priming from seeing a celebrity face to recognizing his or her name was greater than that from seeing a name to recognizing the corresponding face.…”
Section: Face Processing and Memory: Mechanisms Revealed By Behavioramentioning
confidence: 99%
“…However, there is no single or simple answer for the rehabilitation approach in behavioral terms. Some research points to the role of cognitive strategies [ 25 , 26 ]. In this way, it has been described that good recognizers would be distinguished not only by the number of faces they recognize but also by the number of these stimuli that they can reject as unfamiliar [ 27 ].…”
Section: Introductionmentioning
confidence: 99%
“…When it comes to the role of stimulus on face recognition, it is important to remember that position, to some extent, would not entail a high cost, unlike other stimuli, such as written words [ 26 ]. Moreover, in our daily routine, it is common to constantly face different positions for a face in our environment.…”
Section: Introductionmentioning
confidence: 99%